Visual And Metaphorical Representation In McDonald’s Singapore Advertisement - Ditta Eka Rahmadani; Muhammad Hafiz Kurniawan (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
The raise of technology advanced the advertising platform, social media, as one of their ways of offering products that can reach wide audience around the world. This research aims to scrutinize the advertisement of McDonald’s Singapore Instagram account using social semiotic approach and pictorial metaphor theory. This research applied four steps of collecting and analysing 60 multimodal data 1) collecting the data in McDonald’s Singapore account, 2) observing the data, 3) taking data sample, and 4) transcribing and analysing the data. From the analysis, the result of this research shows that conceptual representation dominates the data by 39 data and it is followed by embedding and narrative representation by 19 and 2 data respectively. The compositional meaning was combined with the analysis of pictorial metaphor and the result shows that the non-metaphorical centre is more dominant that others by 15 data, and then it is followed by non-metaphorical tryphtic as many as 13 data, non-pictorial metaphor ideal-real by 8 data, pictorial metaphor tryphtic by 6 data and pictorial metaphor centre by 5 data, while the rest is pictorial metaphor given-new, non-pictorial metaphor given-new, pictorial metaphor ideal-real, and verbo-pictorial metaphor ideal-real by 5, 4, 2, and 2 data respectively.